MIRROR ON THE WALL; Refleksivitas Keberpihakan Media Dalam Pemilihan Presiden Tahun 2014. - Fiandy Mauliansyah (Universitas Teuku Umar, 2016)
This paper wants to examine how media bias in the political process in Indonesia especially in the context of the presidential election in 2014. The study found that in the present political news about the elections, the mass media over use to the theory of journalism, which is based on the values of fame ( prominency) or public figures (public figure) instead of human values (human interest) and public interest (signifcant). So the media often promote norm